VD_FINDINFO HC / 2009 / 12 vom 27. Mai 2009 - VD Tribunal cantonal (2009)
EXPULSION DE LOCATAIRE, NOTIFICATION DE LA DÉCISION, TÉLÉCOPIE, NOTIFICATION PAR HUISSIER | 17 CPC, 26 CPC, 33 CPC, 20 LPEBL, 21 LPEBL